2016
DOI: 10.1177/0149206314525205
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Different Forms of Shared Leadership–Team Performance Relations

Abstract: Using 50 effect sizes from both published and unpublished studies (team n = 3,198), we provide meta-analytic support for the positive relationship between shared leadership and team performance. Employing a random effects model, we found that the theoretical foundation and associated measurement techniques used to index shared leadership significantly moderated effect size estimates. Specifically, as compared to studies that conceptualized and employed assessments of overall shared leadership from members (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
524
4
16

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(567 citation statements)
references
References 96 publications
(149 reference statements)
23
524
4
16
Order By: Relevance
“…Considering the effects of shared leadership on the two previously mentioned types of communication, previous research shows that in terms of 'achievement of goals', shared leadership is also associated with relationship building [32]. Also, Perry, Pearce and Sims [33] state that shared leadership in teams leads to both affective responses as well as behavioral responses.…”
Section: Shared Leadershipmentioning
confidence: 99%
“…Considering the effects of shared leadership on the two previously mentioned types of communication, previous research shows that in terms of 'achievement of goals', shared leadership is also associated with relationship building [32]. Also, Perry, Pearce and Sims [33] state that shared leadership in teams leads to both affective responses as well as behavioral responses.…”
Section: Shared Leadershipmentioning
confidence: 99%
“…However it is possible to observe similar descriptions because of the following facts; (1) focusing on leadership process, (2) the way of defining leadership, (3) the sharing or distributing of leadership, (4) dynamics of leadership process and (5) grounding on multiple roles and functions [3].…”
Section: Leadership Based On Social Interaction; Leadership Ismentioning
confidence: 99%
“…Results of meta-analyses indicate that the interpretation of shared leadership may have an effect on the relationship between shared leadership and team performance. D'Innocenzo et al 36 found a statistically significant difference among the two study techniques, with rating the members providing a stronger overall relationship. Density and centralization measures showed Page 26.1370.4 no significant differences in terms of effect size.…”
Section: Measuring Leadership Sharingmentioning
confidence: 99%
“…[35][36][37][38] By interpreting shared leadership as an emerging, dyadic phenomenon, researchers rate the members through social network analysis of individual team member data. [35][36][37][38] Within the social network analysis, three approaches to measuring leadership sharedness have been used: 1) network centralization (variability of individual indices, 2) network density (number of influence relationships within the team) , and 3) coefficient of variation (variation of team member influence scores). 35 Meta-analyses have not addressed the use of coefficient of variance measures (see 36; 37; 38 ).…”
Section: Measuring Leadership Sharingmentioning
confidence: 99%